Expression and structure of national identity of students of the Faculty of education in Užice measured by Nait scale - Semiz, Marina; Vasilijević, Danijela; Bojović, Žana (Sociološki pregled, 2022)
Many research instruments for measuring the degree of expression and components of national identity have been developed and tested, and one of the most commonly applied instruments in the context of former Yugoslav republics is the NAIT scale developed by Čorkalo and Kamenov. The aim of this study is to examine the degree of expression and structure of national identity among students by testing the multidimensional NAIT scale. This research is based on the assumptions of social identity theory developed by Tajfel and Turner, and starts from the existing psychological and sociological definitions of national identity and research on national identity. The students of the University of Kragujevac, the Faculty of Education, participated in the research (N=175). The research results indicate that the expression of national identity is higher with regard to the theoretical mean, and with regards to the results of some other research. The exploratory factor analysis singled out five components of students’ national identity: 1) national affiliation; 2) national pride and sentiment; 3) relevance of the sense of national belonging; 4) nationalism; and 5) cosmopolitism. Based on the research results, we identified differences in the individual basic dimensions of students’ national identity with regard to previous research.